MAIN APPROACHES TO ORGANISATION OF AN INTERNAL CONTROL SYSTEM IN BANKS OF UKRAINE - Швець, Наталія; Омельчук, Ярослав (Socio-economic relations in the digital society, 2019)
The article outlines the research on the prerequisites for strengthening of internal control procedures in Ukrainian banks. The main approaches to organisation of the internal control system in the banks of Ukraine taking into account regulatory requirements of the National Bank of Ukraine were defined. The key methods and directions for implementation of internal control procedures within functions and operations of the banking institutions of Ukraine were analysed. The main instruments of the internal control, which should be regulated and implemented within functions and operations of the banking institutions, were classified. The criteria for evaluatiion of the internal control system by the banking institutions and the National Bank of Ukraine were outlined. The article brought the attention to the main requirements stated in the Regulation on organisation of the internal control system in the banks and banking groups of Ukraine issued by the National Bank of Ukraine in 2019, in particular ten major changes in organisation of the internal control that will significantly affect the activities of the banking institutions of Ukraine were identified. The components of the internal control system